POLITICAL GRAFFITI AS A TYPE OF POLITICAL COMMUNICATION - Thea Shavladze (International Journal of Innovative Technologies in Social Science, 2025)
The present paper examines political graffiti as a significant form of street art and political communication. This urban expression reflects both contemporary social issues and global tensions, while simultaneously revealing nationalist, racist, and homophobic ideologies. Urban walls serve as valuable research sites, functioning as "litmus paper" that captures major social shifts and eruptions of contradictory opinions. Through this lens, we can observe the visual documentation of both domestic and international political dynamics. This article examines the role of political graffiti in Batumi (a small town in Western Georgia), how graffiti artists shape public discourse, what types of political issues appear in these works, and how the city government responds to political inscriptions.